Quality and Social Responsibility: A view to continuous improvement and excellence in Portuguese Higher Education Institutions, the perspective of the students integrated in mobility programmes - Nogueiro, Teresa (2012)
The Total Quality Management (TQM) is increasingly a need for organizations. The growing social concerns have led organizations to think evolutionarily in quality, especially those wishing to make an approach towards excellence. TQM can be used as a determinant of the development of a corporate culture ethically sensitive. Models such as the European Quality Award and European Foundation for Quality Management incorporate an element of social responsibility and management practices compatible with the defender of the ideals of Corporate Social Responsibility (Ghobadian and Woo, 1996 and Martin-Castilla, 2002, cited by Ghobadian et al., 2007). Institutions of higher education are among the group of institutions that demand excellence. The quality and social responsibility are factors that begin to be part of their strategies. Students from Higher Education Institutions (HEI) integrated in mobility programs, increasingly important stakeholders for these institutions, will have their own perspective on these matters which is important on the evaluation of HEI.